The Posthuman Vision of Philip K. Dick in Do Androids Dream of Electric Sheep? - McInnis, Gilbert (Hungarian Journal of English and American Studies, 2021)
Philip K Dick’s Do Androids Dream of Electric Sheep? explores the notions of the schizoid and the android as prototypes for the posthuman. Dick created androids to represent people physiologically and psychologically behaving in a non-human way, which is the same as Dick’s literal interpretation of a human without empathy—the schizoid. Hence, androids are metaphors for schizoid humans, or posthumans. Furthermore, there is a metaphysical worldview underlying Dick’s notion of empathy which differentiates the posthuman from the human, and this worldview conflicts with the materialistic worldview of the posthumans. Dick supports the metaphysical worldview over the materialistic ideology of the posthuman. The analysis draws primarily on Dick’s novel and three of his later essays to conclude that Dick wrote about the notions of the schizoid and android as prototypes for the posthuman long before anyone had an idea to embark on a full-length study of the posthuman, and Dick’s vision was an insightful warning about the coming implications of the schizoid posthuman for the twenty-first century. (GM)